IMPLEMENTASI PRINSIP-PRINSIP PENGELOLAAN KEUANGAN DAERAH - Steelyana Indriasari; Winarti ' (Universitas Riau, 2013)
Implementation of goodgovernance requires institutional and public management reform. There is a difference in the fieldof financial management reforms and financial management areas. The purpose of this study is todetermine differences in the implementation of the principles in the areas of financial managementin Karanganyar and Sukoharjo region. This study uses a quantitative method using a questionnaireas a data collection tool. The study population is all officials at Regional Secretariat, Department/Agency/Office/Unit financial management area (PPKD, SKPDs) for echelon III, Council BudgetAgency and associated stakeholders. The sampling technique using saturated sampling. Data weretested by using the validity and reliability by using Product Moment correlation and Cronbach 'salpha. Data analysis using a different test with different test techniques on average two independentsamples (t-test). The results showed that different tests are performed using Independent SampleTest (Mann Whitney Test) and the Independent Sample t-Test, it turns out there is a difference inthe implementation of the principles of financial management between Sukoharjo and Karanganyarregion. Sukoharjo turned out better than Karanganyar in the implementation of 3 (three) areas offinancial management principles, namely the principle of accountability, probability and control.The impact of differences in the implementation of the principle of local financial management,making Sukoharjo is able to achieve higher revenue and development expenditure thanKaranganyar region.Keywords : principles of financial management, good governance, implementation, institutionalreforms.